Involvement of calmodulin in regulation of primary root elongation by N-3-oxo-hexanoyl homoserine lactone in Arabidopsis thaliana - Zhao, Qian; Zhang, Chao; Jia, Zhenhua; Huang, Yali; Li, Haili; Song, Shuishan (Frontiers in Plant Science, 2015)
Many bacteria use signal molecules of low molecular weight to monitor their local population density and to coordinate their collective behavior in a process called “quorum sensing” (QS). N-acyl-homoserine lactones (AHLs) are the primary QS signals among Gram-negative bacteria. AHL-mediated QS plays an essential role in diverse bacterial physiological processes. Recent evidence shows that plants are able to sense bacterial AHLs and respond to them appropriately. However, little is known about the mechanism by which plants perceive and transduce the bacterial AHLs within cells. In this study, we found that the stimulatory effect of N-3-oxo-hexanoyl homoserine lactone (3OC6-HSL) on primary root elongation of Arabidopsis was abolished by the calmodulin (CaM) antagonists N-(6-aminohexyl)-5-chloro-1-naphthalene sulfonamide (W-7) and trifluoperazine (TFP). Western-blot and ELISA analysis revealed that the concentration of CaM protein in Arabidopsis roots increased after treatment with 1 μM 3OC6-HSL. Results from quantitative RT-PCR demonstrated that the transcription of all nine CaM genes in Arabidopsis genome was up-regulated in the plants treated with 3OC6-HSL. The loss-of-function mutants of each AtCaM gene (AtCaM1-9) were insensitive to 3OC6-HSL-stimulation of primary root elongation. On the other hand, the genetic evidence showed that CaM may not participates the inhibition of primary root length caused by application of long-chained AHLs such as C10-HSL and C12-HSL. Nevertheless, our results suggest that CaM is involved in the bacterial 3OC6-HSL signaling in plant cells. These data offer new insight into the mechanism of plant response to bacterial QS signals.